Legal Accountability of Budget Authorities in Refocusing Corona Virus Disease 19 - Aprilianti, Rindi; Prakasa, Satria Unggul Wicaksana (Academos, 2022)
ABSTRACTThis study focuses on analyzing the legal accountability of budgetary power in refocusing covid-19. According to data from Indonesia Corruption Watch (ICW), state losses in 2020 amounted to Rp. 18.173 trillion, while in 2021, state losses due to corruption cases amounted to Rp. 26.83 trillion. this is in line with the case of social assistance provided by the government including the PKH (Hope Family Program), the Basic Food Card Program, the Bulog Rice Assistance Program, and the BST (Cash Social Assistance) Program. Related legal issues raised and analyzed, 1) Discussion on legal accountability (KSSK) in the analysis of article 27 paragraph (2) Perppu No.1 of 2020 and 2) Legal efforts in enforcing the COVID-19 budget refocusing. Using social-legal methods. The results of the study based on 1) Article 27 paragraph (2) of Perppu No.1 of 2020 and Government Regulations of Presidential Instruction No. 4 of 2020 show the enforcement of budget refocusing by placing the position of regional heads or executive organs in budgeting and budget execution issues. With criminal justice with imprisonment and fines in accordance with Article 12 letter a of Law of the Republic of Indonesia Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption as amended in Law of the Republic of Indonesia Number 20 of 2001. 2) Strengthening the mechanism of the role of law enforcement in the budget refocusing system is needed by maximizing implementation of the rules of corruption during the Covid-19 pandemic effectively and provide a deterrent effect through a letter of claim.